Are polymorphisms in metabolism protective or a risk for reduced white blood cell counts in a Chinese population with low occupational benzene exposures?. (September 2015) - Ye, Ling-li; Zhang, Guang-hui; Huang, Jing-wen; Li, Yong; Zheng, Guo-qiao; Zhang, De-ting; Zhou, Li-fang; Tao, Xi-dan; Zhang, Jing; Ye, Yun-jie; Sun, Pin; Frank, Arthur; et al.
Abstract : Background: Genetic variations in metabolic enzyme genes may enhance hematotoxicity in benzene-exposed populations. Objective: To investigate the association between polymorphisms of metabolism genes and white blood cells (WBCs). Methods: Three hundred and eighty-five benzene-exposed workers and 220 unexposed indoor workers were recruited in China. We explored the relationship between metabolic enzymes polymorphisms [ glutathione S-transferase T1/M1 ( GSTT1/M1 ) null, glutathione S-transferase P1 ( GSTP1 )rs1695, Cytochrome P450 2E1 ( CYP2E1 ) rs3813867, rs2031920, rs6413432, microsomal epoxide hydrolase (mEH) rs1051740, rs2234922] by polymerase chain reaction (PCR)–restriction fragment length polymorphism (RFLP) analysis and WBC. Results: The exposed group had lower WBC counts ( P <0·001) than the unexposed group. Increased susceptibility to hematotoxicity, as evidenced by lower WBC counts, was found in workers with null- GSTT1 ( P  = 0·045), null- GSTM1 ( P  = 0·030), rs2031920 ( P  = 0·020), and rs3813867 ( P  = 0·014) genotypes. White blood cell counts were also lower in workers with null-GSTT1 and null-GSTM after adjusting for age, gender, smoking, and alcohol consumption. Conclusion: Null- GSTT1 and null- GSTM1 genotypes and Cytochrome P4502E1 (CYP2E1: rs2031920, rs3813867) may support the hematotoxicity of benzene-exposed workers in China, and we can make use of it to select susceptible population.